Вычислите 1)[latex]( \frac{1}{4} \sqrt{12} - \frac{3}{8} \sqrt{27}+0,5 \sqrt{48}- \frac{3}{4} \sqrt{75})4 \sqrt{3} [/latex] 2)[latex] \sqrt{ ( \sqrt{5}- \sqrt{7} )^{2} } - \frac{3}{ \sqrt{7}+2 }+ \sqrt{5} [/latex]

Вычислите 1)[latex]( \frac{1}{4} \sqrt{12} - \frac{3}{8} \sqrt{27}+0,5 \sqrt{48}- \frac{3}{4} \sqrt{75})4 \sqrt{3} [/latex] 2)[latex] \sqrt{ ( \sqrt{5}- \sqrt{7} )^{2} } - \frac{3}{ \sqrt{7}+2 }+ \sqrt{5} [/latex]
Гость
Ответ(ы) на вопрос:
Гость
1) (1/4 √12 - 3/8√27 +0,5√48 - 3/4√75)4√3 = √36 - 1,5*√81 + 2√144 - 3√225 =  = 6 - 1,5 * 9 + 2*12 -3*15 = 6 - 13,5 + 24 - 45 = -28.5 2) [latex] \sqrt{ ( \sqrt{5}- \sqrt{7} ) ^{2}} - \frac{3}{ \sqrt{7}+2}+ \sqrt{5} = ( \sqrt{7} - \sqrt{5} ) - \frac{3}{ \sqrt{7}+2}+ \sqrt{5} = \\ \frac{( \sqrt{7}- \sqrt{5})( \sqrt{7}+2) - 3 + \sqrt{5}( \sqrt{7}+2)}{ \sqrt{7}+2} = \frac{7+2 \sqrt{7}- \sqrt{35}-2 \sqrt{5}- 3+ \sqrt{35}+2 \sqrt{5}}{ \sqrt{7}+2}= \\ \frac{4+2 \sqrt{7}}{ \sqrt{7}+2} = \frac{2(2+ \sqrt{7})}{ \sqrt{7}+2} = 2[/latex]      
Не нашли ответ?
Ответить на вопрос
Похожие вопросы